ANALISA KEBIJAKAN PEMERINTAH INDONESIA TERKAIT ANCAMAN PENGANGGURAN PASCA INFLASI - Davin Ewaldo; Michael Setiawan; Viviana Angesty; Renalbi; Joven Alfando Cang (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
Unemployment and inflation are related problems, common in all countries of the world. This article analyzes the government's policy on inflation-induced unemployment with Indonesia as the object. This article uses quantitative techniques to compare figures from previous years. Poverty rates increase with the number of unemployed, high unemployment rates can lead to lower national incomes in a country. Of course, the crime rate will go up. High inflation is usually caused by large amounts of debt and money in circulation in the country. Inflation also raises the price of commodities and lowers the exchange rate. In 2020, the unemployment rate in Indonesia reached its highest level due to the impact of the new coronavirus infection, which also affected the economic level of Indonesia, and Indonesia experienced a drastic economic decline in 2020.